2006
DOI: 10.1029/2005gb002669
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and origin of the anthropogenic CO2 increase and 13C Suess effect in the Nordic seas since 1981

Abstract: The estimated D 13 C ant and DC ant and their relationship to each other and to water mass distribution suggest that the Polar Water entering the Nordic seas from the north is undersaturated with respect to the present atmospheric anthropogenic CO 2 levels and promotes a local uptake of C ant within the Nordic seas. In contrast, the Atlantic Water entering from the south appears equilibrated. It carries with it anthropogenic carbon which will be sequestered at depth as the water overturns. This preequilibratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
122
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 95 publications
(144 citation statements)
references
References 60 publications
19
122
3
Order By: Relevance
“…In the Nordic seas the disequilibrium has changed over the past twenty years. The work presented by Olsen et al [2006] showed that in the northern regions it appears to have increased while decreasing in the south. As a first-order approximation they found that the annual pCO 2 changes in the upper 500 m of the Nordic seas between 1981 and 2002/2003 could be expressed in terms of salinity: 2.074 × S −71.13, r 2 = 0.6, Figure A3.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the Nordic seas the disequilibrium has changed over the past twenty years. The work presented by Olsen et al [2006] showed that in the northern regions it appears to have increased while decreasing in the south. As a first-order approximation they found that the annual pCO 2 changes in the upper 500 m of the Nordic seas between 1981 and 2002/2003 could be expressed in terms of salinity: 2.074 × S −71.13, r 2 = 0.6, Figure A3.…”
Section: Discussionmentioning
confidence: 99%
“…The transport of DIC ant with this inflow is a key source of DIC ant to the Nordic seas and the present results allows for a rudimentary assessment of the fate of this DIC ant . Olsen et al [2006] estimated an annual influx of 0.12 Gt DIC ant by combining a DIC ant estimate of 53 mmol kg −1 with a volume flux estimate of 6 Sv of NAW flowing into the Nordic seas. Our DIC ant concentration estimates in the NAW are slightly smaller ( Figure 4); 45 mmol kg −1 does not appear unreasonable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations